THE USE OF SONGS AS A STUDY TEXT IN THE PROCESS OF LEARNING THE RUSSIAN LANGUAGE - Abdurahmanova Dilbarhon Abdulxamodovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses the effectiveness of using song material in Russian language classes, the fact that songs are a resonant example of speech, and through singing, language learners lose the fear of making mistakes when communicating in Russian, and for Russian language students it becomes easier to learn the methodology of the language and, of course, to interpret the complexity and diversity of a foreign culture. The versatile nature of the effect of singing helps to use it for various purposes, including in the process of teaching foreign languages to adults and children.